Collaborative Strategic Reading (CSR) and Its Influence on Students’ Reading Comprehension - Sulistyani Sulistyani; Khoiriyah Khoiriyah; Agung Wicaksono; Mahendra Puji Permana Aji (UNIB Press, 2022)
Reading is one of skills of language that must be mastered by students. However, students often face the difficulties to comprehend a text. They have problem to get information from a reading text such as identifying social function, identifying main idea, finding explicit and implied information, finding references, finding synonym and antonym because the students have limited vocabulary. Using pre-experimental quantitative design, namely one group pre- and post-test design, this study was intended to investigate the effect of CSR to the students’ reading comprehension. This research used cluster sampling technique consisting of 35 students. The data value was analyzed using Paired Sample T-test of SPSS Statistic version 23. The data analysis showed that the average score of students’ pre-test was 63.14 while the post-test score was 84.57. The t-test computation collected by comparing the results of pre-test and post-test showed the mean score 21.429 and standard deviation 11.086. The result was t-score -11.435 with the significant (2-tailed) value is lower than 0.05. In conclusion CSR (Collaborative Strategic Reading) has significant influence on students’ reading comprehension.